1997
DOI: 10.1094/mpmi.1997.10.4.506
|View full text |Cite
|
Sign up to set email alerts
|

New Rhizobium leguminosarum Flavonoid-Induced Proteins Revealed by Proteome Analysis of Differentially Displayed Proteins

Abstract: Proteome analysis was used to establish the first two-dimensional protein map of Rhizobium. R. leguminosarum bv. trifolii strain ANU843 was grown in defined medium in the presence and absence of the flavonoid 7,4'-dihydroxyflavone. Over 1,700 constitutive proteins were resolved, representing about 30% of the estimated genomic output. Proteome analysis of flavonoid-treated cells was done to reveal differentially displayed proteins. The results showed that while the global expression pattern of proteins was larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
7

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 93 publications
(70 citation statements)
references
References 54 publications
1
62
0
7
Order By: Relevance
“…The cell pellet was washed twice with 30 mM phosphate potassium buffer pH7, and cellular proteins from the pellet were solubilized as described previously. 32 …”
Section: Preparation Of Protein Extractsmentioning
confidence: 99%
“…The cell pellet was washed twice with 30 mM phosphate potassium buffer pH7, and cellular proteins from the pellet were solubilized as described previously. 32 …”
Section: Preparation Of Protein Extractsmentioning
confidence: 99%
“…Notably, the NodD regulon, comprising luteolin-inducible and NodDdependent genes (Barnett et al 2004;Capela et al 2005), showed that the biosynthesis of NFs is one of the major pathways induced by the luteolin, but not the only one. Indeed, other additional genes are induced by the perception of plant flavonoid signals or show in their promoter region putative binding sites for NodD besides those related to NF biosynthesis (Batista and Hungria 2012;Galardini et al 2011;Lang et al 2008;Guerreiro et al 1997;Tolin et al 2013). Similarly to other plant flavonoids, luteolin was found to induce in E. meliloti, in addition to nod genes, the expression of genes encoding the EmrAB efflux pump, the GroES and GroEL chaperonins, as well as the SyrM transcriptional regulator and three hypothetical proteins (Capela et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Rhizobium strains were grown at 28°C, on a shaker at 200 rpm, in 1 liter of BIII medium (9) . During mid-exponential-phase growth (optical density at 600 nm of 0.5 to 0.6) the cells were harvested, washed and lysed as previously described (17).…”
Section: Fig 1 2-d Protein Array Ofmentioning
confidence: 99%
“…2-DE and electroblotting to polyvinylidene difluoride (PVDF) membranes were done by previously described methods (17). Isoelectric focusing in the first dimension was carried out on linear pH 4 to 7 and nonlinear pH 3 to 10 18-cm immobilized pH gradient (IPG) strips (PharmaciaBiotechnology, Uppsala, Sweden) loaded with 100 g (0.5 to 1 mg for preparative 2-D gels) of total cellular protein and run for 200 kV ⅐ h. N-terminal protein sequencing was done on a PROCISE-HT sequencer system or on a PROCISE-CLC (both from Perkin-Elmer Applied Biosystems, Foster City, Calif.) for verylow-abundance proteins.…”
Section: Fig 1 2-d Protein Array Ofmentioning
confidence: 99%